Educar pela pesquisa: uma proposta metodológica para a alfabetização científica nos anos iniciais do ensino fundamental - Morais, Ponyelen da Silva (2011)
This study has as objective to analyze if educate by research, as a methodology proposal, has viability on scientific alphabetization of Elementary School Initial Years in a public school of Manaus City. The methodology is based in: bibliographical survey, contemplating the thematics educate by research, research and scientific alphabetization; participant research with boarding qualitative and two pedagogical workshops with students in intention to facilitate the process teach-learning. The results signalizes for the possibility of educating by research in Elementary School Initial Years as a innovative proposal of scientific alphabetization.